George Erwin interviewed by Robert Linford in the Parliament's Bicentenary oral history project - Erwin, George Dudley, 1917-1984.; Linford, Robert; Australia. Department of the Parliamentary Library (1984)
Hon. George Erwin speaks about his family background; early interests; his first steps into politics; election campaigns; the Vietnam issue; the relationship between the Liberals and Country Party; about Holt, Gorton, McMahon, Snedden, Fraser; the achievements in social welfare issues; about atomic weapons and energy; his present work and life.
Project administered by the Department of the Parliamentay Library and consists of interviews with retired politicians who speak of their political careers.
Recorded on 4 October 1984.
Also available online
Erwin held the seat of Ballarat (Vic.) for the Liberal Party from December 1955 to November 1975.
Timed transcript and timed summary available.
Keywords: Erwin, George Dudley, -- 1917-1984 -- Interviews; Politicians -- Australia -- Interviews